Light emitting diode based on core-shell composite structure hole blocking layer and preparation method thereof

By using a charge transport layer with a core-shell composite structure in the hole barrier layer of the light emitting diode, the problems of low material conductivity and high carrier concentration are solved, and more efficient charge transport and luminous efficiency are achieved.

CN119451396AInactive Publication Date: 2025-02-14HUAZHONG UNIV OF SCI & TECH

Patent Information

Application Number
CN202411489283.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The low conductivity and excessively high surface carrier concentration of existing light emitting diode materials lead to inefficient charge transfer and low luminous efficiency.

Method used

The hole barrier layer with a core-shell composite structure is adopted to form a charge transport layer of the core-shell structure by depositing charge transport material on the conductive material, thereby increasing the conductivity and reducing the surface carrier concentration.

Benefits of technology

The transmission efficiency of electrons inside the hole barrier layer is significantly improved, non-radiative recombination is reduced, and the luminous efficiency of the light emitting diode is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451396A_ABST
    Figure CN119451396A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of light-emitting diodes, and relates to a light-emitting diode based on a core-shell composite structure hole blocking layer and a preparation method thereof.The light-emitting diode comprises a cathode substrate, the hole blocking layer, a porous insulating layer and a porous anode, wherein the pores of at least one of the hole blocking layer, the porous insulating layer and the porous anode are also filled with a light-emitting active material; the hole blocking layer is composed of a composite material with a core-shell structure, the composite material with the core-shell structure adopts a conductive material as a core layer and a charge transport material as a shell layer, the porous core-shell hole blocking layer is used for replacing a common charge transport material, efficient composite luminescence of current carriers can be achieved, and the hole blocking layer is a porous hole blocking layer. And high-efficiency transmission of charges in a bulk phase can be ensured, and a high-performance light-emitting diode device is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of light emitting diodes, and more specifically, relates to a light emitting diode based on a hole blocking layer of a core-shell composite structure and a preparation method thereof. Background Art

[0002] Since lighting and display devices account for an important share of overall energy consumption, it is particularly important to develop low-energy lighting and display technologies.

[0003] Light-emitting diodes, with their ability to efficiently convert electrical energy into light energy, have the advantages of low energy consumption and high brightness, and play a significant role in reducing the energy consumption of lighting and display. To achieve their widespread application, the key is to manufacture high-performance devices while reducing costs. Using solution processing technology to prepare high-performance light-emitting diodes in an atmospheric environment is an effective cost-reduction strategy. The hole blocking layer is a key functional layer in light-emitting diodes. On the one hand, it blocks the holes transmitted from the positive electrode from further transmitting to the negative electrode, reducing the probability of short circuits inside the light-emitting diode. On the other hand, the hole blocking layer also plays the role of further transmitting electrons from the negative electrode to other functional layers. However, improving the conductivity and transmission capacity of the hole blocking layer is one of the main challenges. Common charge transport materials used in perovskite light-emitting diodes, such as titanium oxide (TiO2) and zinc oxide (ZnO), limit the effective transfer of charges due to their low conductivity, which may lead to charge reflux and non-radiative recombination at the interface, thereby restricting further improvement of device efficiency. Although materials such as indium tin oxide (ITO) and antimony-doped tin oxide (ATO) have high electrical conductivity, their high surface carrier concentration can easily lead to non-radiative recombination and heat release, resulting in large energy loss, which ultimately significantly reduces the luminescence performance. Therefore, it is necessary to improve the bulk conductivity of the material to enhance the overall charge transfer capability, while avoiding excessive surface carrier concentration to inhibit non-radiative recombination and thus improve luminescence efficiency. Summary of the invention

[0004] In view of the defects and improvement needs in the prior art, the present invention provides a light-emitting diode based on a core-shell composite structure hole blocking layer and a preparation method thereof. By depositing a charge transfer material on a conductive layer to form a charge transfer layer with a core-shell structure, the technical problems in the prior art that the low conductivity of the diode material limits the effective transfer of charges, and the non-radiative recombination caused by an excessively high surface carrier concentration, thereby resulting in low luminous efficiency, are solved.

[0005] According to a first aspect of the present invention, a light-emitting diode based on a core-shell composite structure hole blocking layer is provided, the light-emitting diode comprising a cathode substrate and a hole blocking layer, a porous insulating layer and a porous anode sequentially deposited on the cathode substrate, wherein at least one of the hole blocking layer, the porous insulating layer and the porous anode is also filled with a luminescent active material in its pores;

[0006] The hole blocking layer is composed of a composite material with a core-shell structure, wherein the composite material with a core-shell structure uses a conductive material as a core layer and a charge transport material as a shell layer.

[0007] Preferably, the conductive material is one or more of indium tin oxide, silver nanowires, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium zinc oxide, and titanium nitride; the charge transport material is one or more of titanium dioxide, tin oxide, zinc oxide, barium stannate, and fullerene.

[0008] Preferably, it is characterized in that the porous insulating layer is one or more of zirconium dioxide, aluminum oxide, silicon dioxide and barium sulfate.

[0009] Preferably, in the hole blocking layer of the core-shell composite structure, the core layer has a thickness of 95 to 4950 nm, the shell layer has a thickness of 5 to 50 nm, and the porous insulating layer has a thickness of 1 to 4 μm.

[0010] Preferably, the pore size of the hole blocking layer is in the range of 5 to 500 nm, the pore size of the porous insulating layer is in the range of 5 to 500 nm; and the pore size of the porous anode is in the range of 200 to 2000 nm.

[0011] Preferably, the luminescent active material is selected from one or more of metal halide perovskite semiconductor materials, Group III-V semiconductor materials, Group IV-VI semiconductor materials or organic semiconductor materials.

[0012] Preferably, the metal halide perovskite semiconductor material has a general chemical formula of ABX3, wherein A is at least one of methylamine, formamidine, and alkali metal elements, B is at least one of lead and tin, and X is at least one of iodine, bromine, and chlorine; the III-V group semiconductor material is selected from one or more of gallium arsenide, indium phosphide, gallium nitride, indium phosphide, gallium phosphide, aluminum gallium nitrogen, and indium gallium nitrogen; the IV-VI group semiconductor material is selected from one or more of zinc sulfide, cadmium sulfide, lead sulfide, lead telluride, cadmium telluride, and cadmium selenide.

[0013] According to another aspect of the present invention, a method for preparing a light emitting diode based on a hole blocking layer of a core-shell composite structure is provided, comprising the following steps:

[0014] (1) screen printing a conductive material slurry on a cathode substrate to prepare a porous conductive layer on the cathode substrate;

[0015] (2) sintering the porous conductive layer prepared in step (1), immersing it in a dispersion of a charge transport material precursor, and then taking it out and drying it to chemically deposit a charge transport layer material on the surface of the porous conductive layer, thereby constructing a composite material with a core layer and a charge transport material as a shell layer, wherein the composite material with a core-shell structure constitutes a hole blocking layer;

[0016] Alternatively, the porous conductive layer prepared in step (1) is sintered to oxidize the conductive material on the surface of the porous conductive layer to generate a charge transport layer, thereby depositing the charge transport layer on the surface of the porous conductive layer, thereby constructing a composite material with a core layer and a charge transport material as a shell layer, wherein the composite material with a core-shell structure constitutes a hole blocking layer;

[0017] (3) screen-printing a porous insulating layer and a porous anode layer on the hole blocking layer layer by layer, and then sintering the porous insulating layer to form a framework structure of a light-emitting diode;

[0018] (4) applying a drop of a precursor of a luminescent active material onto the light-emitting diode framework structure obtained in step (3), so that the precursor of the luminescent active material penetrates and fills the pores of the porous anode, the porous insulating layer and the hole blocking layer from top to bottom in sequence, and drying and removing the solvent in the precursor to obtain a light-emitting diode based on a core-shell composite structure hole blocking layer.

[0019] Preferably, when the chemical bath deposition method is used to prepare the shell layer in step (2), the conductive material is one or more of indium tin oxide, silver nanowires, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium zinc oxide, and titanium nitride; the charge transport material is one or more of titanium dioxide, tin oxide, zinc oxide, barium stannate, and fullerene; when the sintering method is used to prepare the shell layer in step (2), the conductive material is titanium nitride, and the charge transport material is titanium dioxide.

[0020] Preferably, in step (1), the conductive material slurry is prepared by mixing ethyl cellulose, pine alcohol and conductive material in a mass ratio of 1:2:20 to 10:2:20; in step (2), in the charge transport material precursor dispersion, the charge transport material precursor mass concentration is 0.1%-1%.

[0021] Compared with the prior art, the above technical solutions conceived by the present invention can achieve the following

[0022] Beneficial effects:

[0023] (1) The present invention forms a hole blocking layer with a core-shell structure by depositing a charge transport material on a conductive material. The core layer material has a more excellent electrical conductivity, which can significantly promote the transmission and flow of electrons in the hole blocking layer, reduce the energy loss caused by resistance when electrons pass through the hole blocking layer, and ensure the charge transmission efficiency in the bulk phase; the shell layer material has a lower surface carrier concentration, thereby reducing the non-radiative recombination of electrons and holes at the interface, reducing the energy loss caused by non-radiative recombination, and promoting more freely moving electrons and holes to achieve radiative recombination and luminescence. The core-shell structure composite material is used to promote the efficient transmission and radiative recombination of carriers in the light-emitting diode, thereby improving the overall luminescence efficiency of the light-emitting diode.

[0024] (2) The present invention uses a core-shell structure composite material with a conductive material as the core layer and a charge transport material as the shell layer to form a hole blocking layer. Although the conductive material has good conductivity, which is beneficial to the transmission of electrons inside it, its conduction band position is different from that of the light-absorbing material, which is not conducive to the continued transfer of electrons from the conductive material to the light-absorbing material. The conduction band position of the shell material is generally between the conduction band positions of the conductive material and the light-absorbing material, which can make the electrons transfer from the conduction band of the conductive material to the conduction band of the shell material first, and then finally to the conduction band of the light-absorbing material during the transfer process. This change can effectively change the energy band structure inside the entire light-emitting diode, optimize the transmission process of electrons inside it, reduce the loss during the transmission process, and improve the overall luminous efficiency of the light-emitting diode.

[0025] (3) The present invention limits the thickness of the core layer to 95 to 4950 nm and the thickness of the shell layer to 5 to 50 nm. This is because the thickness of the shell layer should be kept at a relatively thin level to avoid the lateral and longitudinal transmission of electrons in the bulk phase of the hole transport layer. Because the conductivity of the shell layer material is much lower than that of the core layer material, its resistance is greater. A thinner and larger shell layer can reduce the loss of electrons in the shell layer and improve the overall luminous efficiency. The thickness of the porous insulating layer is 1 to 4 μm, which makes the insulating layer have a good insulating effect, and it is not easy for the cathode and the anode to directly contact each other, thus avoiding the short circuit of the overall light-emitting diode. At the same time, it can also avoid the increase of hole losses caused by the transmission process.

[0026] (4) The preparation process of the present invention is simple. Compared with the existing preparation method of light-emitting diodes, it does not require a multi-step and complicated chemical synthesis method. Only a simple one-step chemical bath deposition or oxidation calcination method is required to prepare a hole blocking layer material with a core-shell structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a schematic diagram of the structure of a core-shell hole blocking layer light-emitting diode in an embodiment of the present invention; wherein: 1- cathode substrate, 2- hole blocking layer, 3- porous insulating layer, 4- porous anode.

[0028] Figure 2 This is a photo of the diode light emission of Example 1 of the present invention. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0030] The present invention discloses a light emitting diode based on a porous core-shell structure hole blocking layer and a preparation method thereof, and its structural schematic diagram is shown as follows Figure 1 As shown, it specifically includes a cathode substrate 1 and a hole blocking layer 2, a porous insulating layer 3 and a porous anode 4 deposited in sequence on the cathode substrate 1, wherein at least one of the hole blocking layer 2, the porous insulating layer 3 and the porous anode 4 is also filled with a luminescent active material in its pores; the hole blocking layer 2 is composed of a composite charge transport material with a core-shell structure; the composite charge transport material with a core-shell structure uses a conductive material as a core layer and a charge transport material as a shell layer to form a composite material with a core-shell structure.

[0031] In some embodiments, the cathode substrate 1 is composed of one or more selected from metal elements, inorganic compound conductive materials, heavily doped semiconductor materials, and organic conductive materials.

[0032] In some embodiments, the porous anode 4 is composed of one or more selected from metal elements, inorganic compound conductive materials, heavily doped semiconductor materials, and organic conductive materials.

[0033] In some embodiments, the conductive material is one or more of indium tin oxide (ITO), silver nanowires (AgNWs), fluorine-doped tin oxide (FTO), antimony-doped tin oxide (ATO), aluminum-doped zinc oxide (AZO), gallium zinc oxide (GZO), and titanium nitride (TiN); the charge transport material is one or more of titanium dioxide (TiO2), tin oxide (SnO2), zinc oxide (ZnO), barium stannate (BaSnO3), and fullerene.

[0034] In some embodiments, the particle size of the conductive material is 5 to 500 nm, preferably 20 to 50 nm, and the particle size of the charge transport material is 5 to 500 nm, preferably 20 to 50 nm.

[0035] In some embodiments, the core-shell structure composite hole blocking layer has a core layer thickness of 95 to 4950 nm and a shell layer thickness of 5 to 50 nm. In some embodiments, the material of the porous insulating layer 3 is one or more of zirconium oxide (ZrO2), aluminum oxide (A12O3), silicon oxide (SiO2), and barium sulfate (BaSO4), with a particle size of 5 to 500 nm and a thickness of 1 to 4 μm.

[0036] In some embodiments, the luminescent active material is selected from one or more of metal halide perovskite semiconductor materials, Group III-V semiconductor materials, Group IV-VI semiconductor materials or organic semiconductor materials, wherein the metal halide perovskite semiconductor material has a general chemical formula of ABX3, wherein A is at least one of methylamine, formamidine, and alkali metal elements, B is at least one of lead and tin, and X is at least one of iodine, bromine, and chlorine; the Group III-V semiconductor material is selected from one or more of gallium arsenide, indium phosphide, gallium nitride, indium phosphide, gallium phosphide, aluminum gallium nitrogen, and indium gallium nitrogen; the Group IV-VI semiconductor material is selected from one or more of zinc sulfide, cadmium sulfide, lead sulfide, lead telluride, cadmium telluride, and cadmium selenide.

[0037] According to another aspect of the present invention, a method for preparing a light-emitting diode device based on a core-shell composite structure hole blocking layer is as follows: a porous conductive layer is screen-printed on a cathode substrate 1, and then a charge transfer shell layer is deposited on the surface of the porous conductive layer by a chemical bath deposition method or a sintering method to form a hole blocking layer 2 of a core-shell composite structure; then, a porous insulating layer 3 and a porous anode 4 are prepared in sequence from bottom to top by screen printing; finally, each layer is sintered at a high temperature to form a mesoporous structure; and then a precursor of a luminescent active material is dripped onto the porous anode, and after it is fully penetrated from top to bottom into the pores of the porous anode 4, the porous insulating layer 3, the hole blocking layer 2 and the cathode substrate 1, it is dried.

[0038] In some embodiments, sintering can be carried out by sintering once for each layer deposited, or by sintering after depositing multiple layers (such as two or more layers). For example, sintering can be carried out once after depositing a porous hole blocking layer, and sintering can be carried out again after depositing a porous insulating layer and a porous anode.

[0039] Example 1

[0040] A perovskite light-emitting diode based on a core-shell structure composite material with ITO as the core layer and TiO2 as the shell layer as the hole blocking layer.

[0041] The specific preparation steps are as follows:

[0042] (1) The device uses conductive glass as the cathode substrate 1, uses ITO nanocrystalline particles with a particle size of about 30 nm, ethyl cellulose and pinene alcohol, and prepares an ITO slurry with a certain viscosity in a mass ratio of 1:2:20. A screen printer is used to print a layer of ITO slurry on the cathode substrate 1 by screen printing, and then it is sintered at 500°C to form a porous conductive layer with a thickness of about 800 nm on the cathode substrate 1.

[0043] (2) Subsequently, the porous conductive layer is immersed in an isopropanol solution with a mass concentration of 0.1% titanium tert-butoxide for 2 hours. After drying, a TiO2 shell layer of about 5 nm is formed on the surface of the porous conductive layer, and finally a composite hole blocking layer 2 with an ITO-TiO2 core-shell structure is obtained on the cathode substrate 1.

[0044] (3) ZrO2 nanocrystalline particles with a particle size of about 50 nm, ethyl cellulose and pinene alcohol are used to prepare a ZrO2 slurry with a certain viscosity in a mass ratio of 2:1:4, and graphite flakes with a particle size of 3 μm, carbon black of 30 nm, ethyl cellulose and pinene alcohol are used to prepare a carbon slurry with a certain viscosity in a mass ratio of 13:4:3:45. A screen printer is used to place the prepared slurry on a screen at room temperature, and a substrate is placed under the screen. A scraper is used to print the ZrO2 slurry and the carbon slurry on the hole blocking layer 2 respectively, and the sintering treatment is performed at a high temperature of 400°C to form a porous insulating layer 3 with a thickness of 2 μm and a porous anode 4 with a thickness of about 30 μm.

[0045] (4) A certain amount of 3 μL of iodine lead methylamine (CH3NH3Pbl3) precursor solution (1 mol / L) is dropped onto the porous anode and allowed to stand for 10 minutes to fully penetrate into the pores of the porous anode 4, the porous insulating layer 3, the hole blocking layer 2 and the cathode substrate 1 from top to bottom, and then dried at 60°C.

[0046] A voltage is applied between the two electrodes of the prepared device, and the luminescence of the device is observed using an infrared camera. Figure 2 As shown, the perovskite light-emitting diode device based on the core-shell structure composite material as the hole blocking layer achieved uniform light emission.

[0047] Example 2

[0048] Perovskite light-emitting diode based on a core-shell composite material with TiN as the core layer and TiO2 as the shell layer as the hole blocking layer

[0049] The preparation steps are as follows:

[0050] (1) The device uses conductive glass as the cathode substrate 1, and prepares TiN nanocrystalline particles with a uniform and stable particle size of 30 nm, ethyl cellulose, and pinene alcohol in a mass ratio of 1:2:20 to form a slurry with a certain viscosity. A screen printer is used to place the prepared slurry on the screen at room temperature, and the cathode substrate is placed under the screen. The TiN slurry is evenly printed on the cathode substrate 1 using a scraper wire to prepare a TiN porous conductive layer with a thickness of 800 nm.

[0051] (2) The porous conductive layer is then placed in an oxygen atmosphere and sintered at 400°C to oxidize the surface of the TiN core layer and form a TiO2 charge transfer shell layer with a certain thickness of 5 nm, thereby forming a hole blocking layer 2 with a core-shell composite structure.

[0052] (3) ZrO2 nanocrystalline particles with a particle size of about 50 nm, ethyl cellulose and pinene alcohol are used to prepare a ZrO2 slurry with a certain viscosity in a mass ratio of 2:1:4, and graphite flakes with a particle size of 3 μm, carbon black of 30 nm, ethyl cellulose and pinene alcohol are used to prepare a carbon slurry with a certain viscosity in a mass ratio of 15:4:3:45. A screen printer is used to place the prepared slurry on a screen at room temperature, and a substrate is placed under the screen. A scraper is used to print the ZrO2 slurry and the carbon slurry on the hole blocking layer 2 respectively, and the sintering treatment is performed at a high temperature of 400°C to form a porous insulating layer 3 with a thickness of 2 μm and a porous anode 4 with a thickness of about 40 μm.

[0053] (4) A certain amount of 4 μL of bromolead methylamine (CH(NH2)2PbBr3) precursor solution (1 mol / L) was dripped onto the porous anode, and allowed to stand for 10 minutes until it fully penetrated the porous membrane from top to bottom, and then dried at 60°C. A voltage was applied between the two electrodes of the prepared device, and the luminescence of the device was observed using an infrared sensitive camera. The perovskite light-emitting diode device based on the core-shell structure composite material as the hole blocking layer achieved uniform luminescence.

[0054] Example 3

[0055] A perovskite light-emitting diode based on a core-shell structure composite material with ITO as the core layer and SnO2 as the shell layer as the hole blocking layer.

[0056] The specific preparation steps are as follows:

[0057] (1) The device uses conductive glass as the cathode substrate 1, uses ITO nanocrystalline particles with a particle size of about 30 nm, ethyl cellulose and pinene alcohol, and prepares an ITO slurry with a certain viscosity in a mass ratio of 1:2:20. A screen printer is used to print a layer of ITO slurry on the cathode substrate 1 by screen printing, and then it is sintered at 500°C to form a porous conductive layer with a thickness of about 800 nm on the cathode substrate 1.

[0058] (2) Subsequently, the porous conductive layer was immersed in an isopropanol solution with a mass concentration of 0.1% tin tert-butylate for 2 hours. After drying, a SnO2 shell layer of about 5 nm was formed on the surface of the porous conductive layer, and finally a composite hole blocking layer 2 of an ITO-SnO2 core-shell structure was obtained on the cathode substrate.

[0059] (3) Using ZrO2 nanocrystalline particles with a particle size of about 50nm, ethyl cellulose and pinene alcohol, a certain viscosity ZrO2 slurry is prepared in a mass ratio of 2:1:4, and using graphite flakes with a particle size of 3μm, carbon black of 30nm, ethyl cellulose and pinene alcohol, a certain viscosity carbon slurry is prepared in a mass ratio of 10:4:3:45. Using a screen printer, at room temperature, the prepared slurry is placed on a screen, and the substrate is placed under the screen. Using a scraper, the ZrO2 slurry and the carbon slurry are printed on the hole blocking layer 2 respectively, and sintered at a high temperature of 400°C to form a porous insulating layer 3 with a thickness of 2μm and a porous anode 4 with a thickness of about 20μm.

[0060] (4) A certain amount of 2 μL of cesium lead bromine (CsPbBr3) precursor solution (0.3 mol / L) is dropped onto the porous anode, and allowed to stand for 10 minutes to fully penetrate into the pores of the porous anode 4, the porous insulating layer 3, the hole blocking layer 2 and the cathode substrate 1 from top to bottom, and then dried at 60°C.

[0061] A voltage was applied between the two electrodes of the prepared device, and the luminescence of the device was observed using an infrared sensitive camera. The perovskite light-emitting diode device based on the core-shell structure composite material as a hole blocking layer achieved uniform luminescence.

[0062] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A light-emitting diode based on a core-shell composite structure hole blocking layer, characterized in that: The light-emitting diode comprises a cathode substrate (1) and a hole blocking layer (2), a porous insulating layer (3) and a porous anode (4) sequentially deposited on the cathode substrate (1), wherein the holes of at least one of the hole blocking layer (2), the porous insulating layer (3) and the porous anode (4) are also filled with a light-emitting active material; The hole blocking layer (2) is composed of a composite material with a core-shell structure, wherein the composite material with a core-shell structure uses a conductive material as a core layer and a charge transport material as a shell layer.

2. The light-emitting diode based on the hole blocking layer of the core-shell composite structure according to claim 1, characterized in that: The conductive material is one or more of indium tin oxide, silver nanowires, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium zinc oxide, and titanium nitride; the charge transport material is one or more of titanium dioxide, tin oxide, zinc oxide, barium stannate, and fullerene.

3. The light-emitting diode based on the hole blocking layer of the core-shell composite structure as claimed in claim 1, characterized in that: The porous insulating layer (3) is one or more of zirconium dioxide, aluminum oxide, silicon dioxide, and barium sulfate.

4. The light-emitting diode based on the hole blocking layer of the core-shell composite structure as claimed in claim 1, characterized in that: In the hole blocking layer (2), the core layer thickness is 95 to 4950 nm, and the shell layer thickness is 5 to 50 nm; the porous insulating layer (3) thickness is 1 to 4 μm.

5. The light-emitting diode based on the hole blocking layer of the core-shell composite structure as claimed in claim 1, characterized in that: The pore size of the hole blocking layer (2) is in the range of 5 to 500 nm, the pore size of the porous insulating layer (3) is in the range of 5 to 500 nm; and the pore size of the porous anode (4) is in the range of 200 to 2000 nm.

6. The light-emitting diode based on the hole blocking layer of the core-shell composite structure according to claim 1, characterized in that: The luminescent active material is selected from one or more of metal halide perovskite semiconductor materials, Group III-V semiconductor materials, Group IV-VI semiconductor materials or organic semiconductor materials.

7. The light-emitting diode based on the hole blocking layer of the core-shell composite structure as claimed in claim 6, characterized in that: The metal halide perovskite semiconductor material has a general chemical formula of ABX3, wherein A is at least one of methylamine, formamidine, and alkali metal elements, B is at least one of lead and tin, and X is at least one of iodine, bromine, and chlorine; the III-V group semiconductor material is selected from one or more of gallium arsenide, indium phosphide, gallium nitride, indium phosphide, gallium phosphide, aluminum gallium nitrogen, and indium gallium nitrogen; the IV-VI group semiconductor material is selected from one or more of zinc sulfide, cadmium sulfide, lead sulfide, lead telluride, cadmium telluride, and cadmium selenide.

8. The method for preparing a light-emitting diode based on a hole blocking layer of a core-shell composite structure according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) screen printing a conductive material slurry on a cathode substrate to prepare a porous conductive layer on the cathode substrate; (2) sintering the porous conductive layer prepared in step (1), immersing it in a dispersion of a charge transport material precursor, and then taking it out and drying it to chemically deposit a charge transport layer material on the surface of the porous conductive layer, thereby constructing a composite material with a core layer and a charge transport material as a shell layer, wherein the composite material with a core-shell structure constitutes a hole blocking layer; Alternatively, the porous conductive layer prepared in step (1) is sintered to oxidize the conductive material on the surface of the porous conductive layer to generate a charge transport layer, thereby depositing the charge transport layer on the surface of the porous conductive layer, thereby constructing a composite material with a core layer and a charge transport material as a shell layer, wherein the composite material with a core-shell structure constitutes a hole blocking layer; (3) screen-printing a porous insulating layer and a porous anode layer on the hole blocking layer layer by layer, and then sintering the porous insulating layer to form a framework structure of a light-emitting diode; (4) applying a drop of a precursor of a luminescent active material onto the light-emitting diode framework structure obtained in step (3), so that the precursor of the luminescent active material penetrates and fills the pores of the porous anode, the porous insulating layer and the hole blocking layer from top to bottom in sequence, and drying and removing the solvent in the precursor to obtain a light-emitting diode based on a core-shell composite structure hole blocking layer.

9. The method for preparing a light-emitting diode based on a hole-blocking layer of a core-shell composite structure according to claim 8, characterized in that: When the shell layer is prepared by chemical bath deposition in step (2), the conductive material is one or more of indium tin oxide, silver nanowires, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium zinc oxide, and titanium nitride; the charge transport material is one or more of titanium dioxide, tin oxide, zinc oxide, barium stannate, and fullerene; when the shell layer is prepared by sintering in step (2), the conductive material is titanium nitride, and the charge transport material is titanium dioxide.

10. The method for preparing a light-emitting diode based on a hole-blocking layer of a core-shell composite structure according to claim 8, characterized in that: In step (1), the conductive material slurry is prepared by mixing ethyl cellulose, pine alcohol and conductive material in a mass ratio of 1:2:20 to 10:2:20; in step (2), in the charge transport material precursor dispersion, the charge transport material precursor mass concentration is 0.1%-1%.

Citation Information

Patent Citations

  • Quantum dot light emitting diode, display device and light emitting source

    CN114551735A

  • Solar cell based on core-shell charge transport layer and preparation method thereof

    CN117255575A

  • 3D injection type electroluminescent device and wet preparation method thereof

    CN117615598A

  • Core-shell type nanocomposites included fullerene particle using barrier layer of hole transport layer and preparation method thereof, and solar cell comprising the same

    KR1020150080296A

  • Light-emitting diode comprising surface modified zinc oxide as material for electron transport layer

    KR1020150121355A

Cited By

  • Perovskite battery with transverse structure, preparation method of perovskite battery and perovskite battery assembly

    CN120265004A